P82 Thrombectomy for primary isolated distal anterior cerebral artery occlusion stroke. (29th August 2022) - Meyer, L; Broocks, G; Fiehler, J; Hanning, U
Abstract : Introduction: Distal medium-vessel occlusions (DMVO) stroke represents a possible next frontier of endovascular stroke treatment. However, evidence suggesting a possible benefit remains sparse, especially in the anterior cerebral artery (ACA). 1 2 Aim of study: To investigate clinical and safety outcomes of primary isolated ACA occlusion stroke treated with thrombectomy. Methods: Patients with primary isolated DMVO of the ACA distal to the A1 segment treated endovascularly in daily clinical practice between January, 2013, to October, 2021 were analyzed from an international, retrospective, multicenter registry. 3 4 Early clinical and long-term functional outcome were measured with NIHSS and mRS. Safety was assessed by the occurrence of sICH and mortality. Results: ACA-DMVOs were located in 59.5% (50) in the A2, in 36.9% (31) in the A3 segment, and in 3.6% (3) in the A4 segment. The median age was 76 years (IQR:66–84) and 47.6% (40) were female. The median number of reperfusion attempts was 1 (IQR, 1–2) and in 82.1% (69) of cases thrombectomy was considered successful reaching a reperfusion grade of mTICI 2b-3 including a first-pass effect of 45.2% (38). The median 24h-NIHSS decrease from admission was -2 (IQR: -4 to 1; p=0.033) following thrombectomy. Rates of favorable functional outcome (mRS 0–2) and mortality were 39.1% (25) and 26.6% (17), respectively. SICH occurred in 2.4% (2). Conclusion: Thrombectomy appears technically feasible and safe for treating primary isolated anterior cerebral artery occlusions distal to the A1 segment. Further studies are warranted to evaluate treatment effects. References: Saver JL, Chapot R, Agid R, et al . Thrombectomy for distal, medium vessel occlusions. Stroke 2020;0 (0):Strokeaha.120.028956. DOI: DOI:10.1161/Strokeaha.120.028956 Goyal M, Cimflova P, Ospel JM, et al . Endovascular treatment of anterior cerebral artery occlusions. Journal of Neurointerventional Surgery 2021;13 (11):1007–11. DOI: 10.1136/Neurintsurg-2021-017735 Meyer L, Stracke CP, Wallocha M, et al . Thrombectomy for secondary distal, medium vessel occlusions of the posterior circulation: seeking complete reperfusion. J Neurointerv Surg 2021 DOI: 10.1136/Neurintsurg-2021-017742 Meyer L, Stracke CP, Jungi N, et al . Thrombectomy for Primary Distal Posterior Cerebral Artery Occlusion Stroke: The Topmost Study. Jama Neurol 2021 DOI: 10.1001/Jamaneurol.2021.0001 Do you have any conflict of interest to declare? : No